Respiratory dysfunction in a mouse model of spinocerebellar ataxia type 7 - Anna F. Fusco; Logan A. Pucci; Pawel M. Switonski; Debolina D. Biswas; Angela L. McCall; Amanda F. Kahn; Justin S. Dhindsa; Laura M. Strickland; Albert R. La Spada; Mai K. ElMallah (The Company of Biologists, 2021)
Spinocerebellar ataxia type 7 (SCA7) is an autosomal-dominant neurodegenerative disorder caused by a CAG repeat expansion in the coding region of the ataxin-7 gene. Infantile-onset SCA7 patients display extremely large repeat expansions (>200 CAGs) and exhibit progressive ataxia, dysarthria, dysphagia and retinal degeneration. Severe hypotonia, aspiration pneumonia and respiratory failure often contribute to death in affected infants. To better understand the features of respiratory and upper airway dysfunction in SCA7, we examined breathing and putative phrenic and hypoglossal neuropathology in a knock-in mouse model of early-onset SCA7 carrying an expanded allele with 266 CAG repeats. Whole-body plethysmography was used to measure awake spontaneously breathing SCA7-266Q knock-in mice at baseline in normoxia and during a hypercapnic/hypoxic respiratory challenge at 4 and 8 weeks, before and after the onset of disease. Postmortem studies included quantification of putative phrenic and hypoglossal motor neurons and microglia, and analysis of ataxin-7 aggregation at end stage. SCA7-266Q mice had profound breathing deficits during a respiratory challenge, exhibiting reduced respiratory output and a greater percentage of time in apnea. Histologically, putative phrenic and hypoglossal motor neurons of SCA7 mice exhibited a reduction in number accompanied by increased microglial activation, indicating neurodegeneration and neuroinflammation. Furthermore, intranuclear ataxin-7 accumulation was observed in cells neighboring putative phrenic and hypoglossal motor neurons in SCA7 mice. These findings reveal the importance of phrenic and hypoglossal motor neuron pathology associated with respiratory failure and upper airway dysfunction, which are observed in infantile-onset SCA7 patients and likely contribute to their early death.